2019
DOI: 10.1029/2019gl081956
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Economic Losses From European Floods by the North Atlantic Oscillation

Abstract: The space‐time structure of flood losses is arguably related to large‐scale climatic patterns; however, this interconnection is not always well understood. Here we show that the North Atlantic Oscillation (NAO) correlates with the occurrence of catastrophic floods across Europe and the associated economic losses. The analysis reveals that in Northern Europe the majority of historic winter floods occurred during a positive NAO state, whereas the majority of summer floods occurred during a negative state. Analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 43 publications
1
43
0
Order By: Relevance
“…6), the important drivers of evaporation processes in the 21st century (e.g., precipitation, nearsurface air temperature, wind speed and soil moisture) tend to be not affected by the modes of climate variability in the models. For example, the response of regional evaporation to climate warming depends on precipitation (Parr et al, 2016;Zhang et al, 2018), and a projected rise of surface temperature is shown to mainly contribute to the increase in regional evaporation (Laîné et al, 2014). Because the volume of moisture carried by air increases with air temperature, the atmospheric water vapor demand is expected to increase with ris-ing air temperature and rising greenhouse gases concentration (Miralles et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…6), the important drivers of evaporation processes in the 21st century (e.g., precipitation, nearsurface air temperature, wind speed and soil moisture) tend to be not affected by the modes of climate variability in the models. For example, the response of regional evaporation to climate warming depends on precipitation (Parr et al, 2016;Zhang et al, 2018), and a projected rise of surface temperature is shown to mainly contribute to the increase in regional evaporation (Laîné et al, 2014). Because the volume of moisture carried by air increases with air temperature, the atmospheric water vapor demand is expected to increase with ris-ing air temperature and rising greenhouse gases concentration (Miralles et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In northern Europe, during winter months rainfall variability is strongly modulated by the NAO and the EA, in which their positive phases are linked to higher than average and more intense extreme rainfall in the United Kingdom, Ireland, and in the Scandinavian countries (Casanueva et al, 2014;Guimarães Nobre et al, 2017). In addition, the combination of positive SOI and negative NAO has previously been linked with increased precipitation and high peak discharges in northern European regions in summer (Shaman, 2014;Zanardo et al, 2019), whereas negative EAWR is related to wetter autumns in the latter regions (Casanueva et al, 2014). Similarly, we also observe that the likelihood of Low Damaging floods may increase when indices of atmospheric oscillations are at their extreme phases, which indicates that some of the oscillations may intensify each other influence on flood damages.…”
Section: 1029/2019ef001450mentioning
confidence: 99%
“…For example, there has been successful identification and prediction of climate on subseasonal to decadal timescales, and this can be used to inform the development of tools to alleviate the impact of weather and climate hazards. For example, skillful prediction of the North Atlantic Oscillation could inform hurricane risk and coastal adaptation decisions along the Susquehanna River (Toomey et al 2019) or financial preparedness and disaster fund allocation for floods in Europe (Zanardo et al 2019). In order to use these forecasts, however, planners must embrace uncertainty and develop decision frameworks that make use of probabilistic information at many timescales.…”
Section: Toward Constructive Narrativesmentioning
confidence: 99%